The three-dimensional graphic method for quantifying body position - Trochim, William M K (Behavior Research Methods, 1976)
The three-dimensional graphic method for quantifying body position is a series of observer procedures and computer programs designed to yield three-dimensional (height, width, and depth) coordinates for various body points. These coordinates can be graphed by computer in several different ways, and can be analyzed mathematically to provide information about a wide variety of variables, including interpersonal distance and body activity. The procedure for collecting and analyzing the data is explained and the computer programs developed for the method are described. © 1976 Psychonomic Society, Inc.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/005-192-913-625-728 tex.type: [object Object]
Keywords: dept.psy

Normal development and psychopathological impairment of the concept of the object on the Rorschach. - Blatt, Sidney J.; Brenneis, C. Brooks; Schimek, Jean G.; Glick, Marion (Journal of Abnormal Psychology, 1976)
103 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1976CB12400004 tex.unique-id: [object Object]
Keywords: dept.psy